(U-Th)/He Geochronology Constraints on Lateritic Duricrust Formation on the Guiana Shield - Ansart, C.; Quantin, C.; Calmels, D.; Allard, T.; Roig, J. Y.; Coueffe, R.; Heller, B.; Pinna-Jamme, R.; Nouet, J.; Reguer, S.; Vantelon, D.; Gautheron, C. (Frontiers in Earth Science, 2022)
Thick regoliths developed under tropical climate, namely laterites, result from long-term and pronounced geochemical and mineralogical rearrangement in response to environmental changes. Only few information is available on the timing of laterite and bauxite formations, especially on the chronology of the main weathering episodes responsible for lateritic cover formation on the Guiana shield. For this purpose, we focused on both lateritic and bauxitic duricrusts developed over the Paleoproterozoic Greenstone Belt in the Brownsberg, Suriname. The duricrust samples have relatively simple mineralogy (i.e. goethite, gibbsite, hematite and kaolinite) but reveal when observed at a microscopic scale, a complex history of formation with multiple episodes of dissolution/reprecipitation. The (U-Th)/He dating of 179 Fe-oxides subsamples shows that duricrusts sampled at the top of the Brownsberg plateau have ages ranging from <0.8 Ma to ~19 Ma. In contrast, Fe-oxides extracted from detrital duricrust boulders collected downslope indicate formation ages up to 36 Ma. This age discrepancy may indicate that a main episode of physical erosion affected this region between ca. 30 and 20 Ma. Consistently, the bauxite sampled at the mountaintop indicates a younger phase of formation, with Fe-oxides recementing fragments of a preexisting bauxitic material older than ~15 Ma. Geochronological data also reveal a long-lasting weathering history until the present day, with multiple generations of Fe oxides in the bauxite and the duricrusts resulting from successive cycles of dissolution and reprecipitation of Fe-oxides associated with redox cycles. This long-lasting weathering history led to geochemical remobilization and apparent enrichment in some relatively immobile elements, such as REE, aluminum and vanadium, especially in the duricrust sampled at the mountaintop. Our geochronological, mineralogical and geochemical study of Fe- and Al-crusts from the Brownsberg mountain provide constraints on the evolution of environmental conditions prevailing since the early Oligocene in Suriname.